Evaluation of the privacy concept in traditional houses through the interaction of street and facade using isovist areas: The case of Tokat houses - Sahin, Murat (Nilay Ozsavas Ulucay, 2025)
Traditional houses, shaped and transformed according to the needs of individuals and societies, are influenced by the physical and socio-cultural characteristics of their respective regions. The concept of privacy has played a decisive role in traditional dwellings' spatial organization and facade design, also shaping users' perception of privacy in their interaction with the street. In this context, the study examines how privacy affects the visual connection and field of view between users and the street in traditional houses. The study area focuses on the traditional houses of Tokat, which have largely preserved their original character and texture. In this context, nine traditional houses with different cumba types located on Bey Street and Beyhamam Street were examined. In the study, isovist analysis, a method that enables analysis based on the field of view, was employed. In this context, the visual connections between the street and different floors of traditional houses were calculated, and their effects on the perception of privacy were analyzed. The findings revealed that, depending on the type of cumba, the visual connection with the street is stronger at the ground floor level in traditional houses; however, privacy is not entirely compromised, and the visual relationship varies quantitatively between floors.
Keywords: Traditional housing; Privacy; Cultural heritage; Isovist; Tokat